Cognitive stimulation therapy as a low-resource intervention for dementia in sub-Saharan Africa (CST-SSA): Adaptation for rural Tanzania and Nigeria. (May 2018) - Mkenda, Sarah; Olakehinde, Olaide; Mbowe, Godfrey; Siwoku, Akeem; Kisoli, Aloyce; Paddick, Stella-Maria; Adediran, Babatunde; Gray, William K; Dotchin, Catherine L; Adebiyi, Akinpelumi; Walker, Richard W; Mushi, Declare; et al.
Introduction: Cognitive stimulation therapy is a non-pharmacological intervention for people with dementia. Its use has been associated with substantial improvements in cognition and quality of life in studies from high-income countries, equivalent to those achieved by pharmacological treatments. Cognitive stimulation therapy may be particularly suited to low resource settings, such as sub-Saharan Africa, because it requires little specialist equipment and can be delivered by non-specialist health workers. The aim of this study was to adapt cognitive stimulation therapy for use in sub-Saharan Africa taking into account socio-cultural differences and resource implications. Methods: Cognitive stimulation therapy is a structured programme, originally developed in the United Kingdom. Substantial adaptations were required for use in sub-Saharan Africa. The formative method for adapting psychotherapy was used as a framework for the adaption process. The feasibility of using the adapted cognitive stimulation therapy programme to manage dementia was assessed in Tanzania and Nigeria in November 2013. Further adaptations were made following critical appraisal of feasibility. Results: The adapted cognitive stimulation therapy intervention appeared feasible and acceptable to participants and carers. Key adaptations included identification of suitable treatment settings, task adaptation to accommodate illiteracy and uncorrected sensory impairment, awareness of cultural differences and usage of locally available materials and equipment to ensure sustainability. Conclusions: Cognitive stimulation therapy was successfully adapted for use in sub-Saharan Africa. Future work will focus on a trial of cognitive stimulation therapy in each setting.